MAKNA MANGULOSI PADA ACARA ADAT PERNIKAHAN SUKU BATAK TOBA DI DURI - Kristina, Julia; Yusuf, Yusmar (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2019)
Forthe Batak people, Ulos are cloth or objects which is considered important for their lives. LiterellyUlos has the meaning of of “blanket”. In ancient times Ulos inside used ancestors to warm theirs boodies from the cold. As time goes by to date Ulos is used for every event in the Batak community, both the birth, marriage, and death. Giving Ulos is known as mangulosi. Mangulosi or giving Ulos has simbolic meaning namely giving love from the gover to the recipient. In weddings that used Batak customs there will be a stage of mangulosi to the bride and groom. This mangulosi event has also been adopted to religions in Indonesia. The subject of this study corsisted of five informants, where the subject of this research is the chairman of the clan and also a married people in Duri city.Technique of determining informants in thin study using purposive sampling. The research method used is descriptive qualitative. The theory used is simbolic interactional theory and also theories of social changes. The results of this mangulosi research are mangulosican not be released from the Batak community. Batak brides are said to have been officially married after upgrading this mangulosi. Keywords: Mangulosi, Simbolic interactional, social change.